Gerhard Kessler's Contribution to the Sociological Understanding in Turkey - Bas, Muhammed Fazil (ISTANBUL UNIV, FAC LETTERS, DEPT SOCIOLOGY, 2014)
This article aims to show the roots of Gerhard Kessler's understanding of sociology in the German intellectual tradition and also its influences in Turkey. Kessler was one of the academicians prosecuted in Germany right after the Nazi ideology had seized power, and was also among refugee-professors thanks to the 1933 Turkish University Reform. In the article, Kessler's biography, the German intellectual tradition he was influenced by, his understanding of sociology and also the influence of this understanding in Turkey have been covered. While evaluating Kessler's studies in Turkey, the sociological tradition in Turkey was taken into consideration and also comparisons were made between sociologies of Kessler and Ziya Gokalp. Kessler's main academic formation in social policy was a result of the fact that he was an academician of a class-based society. Following his arrival into Turkey, Kessler dealt with issues regarding the social structure of Turkey. Besides this, he lectured a sociological understanding based on, what he calls, the theory of social relations. His works presented also an approach of liberal collectivism which originated in social liberalism in Germany.
Keywords: Gerhard Kessler; Sociology; Social Policy; German Historical School of Economics; German Professors in Turkey